The subjective meaning of cognitive architecture: a Marrian analysis - Varma, Sashank (Frontiers in Psychology, 2014)
Marr famously decomposed cognitive theories into three levels. Newell, Pylyshyn, and Anderson offered parallel decompositions of cognitive architectures, which are psychologically plausible computational formalisms for expressing computational models of cognition. These analyses focused on the objective meaning of each level – how it supports computational models that correspond to cognitive phenomena. This paper develops a complementary analysis of the subjective meaning of each level – how it helps cognitive scientists understand cognition. It then argues against calls to eliminatively reduce higher levels to lower levels, for example in the name of parsimony. Finally, it argues that the failure to attend to the multiple meanings and levels of cognitive architecture contributes to the current, disunified state of theoretical cognitive science.